2007
DOI: 10.1175/2007jpo3527.1
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Oscillatory Modes of the Argentine Basin. Part I: Statistical Analysis

Abstract: Observations of the sea surface height in the Argentine Basin indicate that strong variability occurs on a time scale of 20Ϫ30 days. The aim of this study is to determine the physical processes responsible for this variability. First, results are presented from two statistical techniques applied to a decade of altimetric data. A complex empirical orthogonal function (CEOF) analysis identifies the recently discovered dipole mode as the dominant mode of variability. A principal oscillation pattern (POP) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In the first part of this study (Weijer et al 2007, hereinafter Part I), statistical analyses of altimeter data suggested that more than one mode of variability may be present in the Argentine Basin. This conclusion may reconcile several studies reporting on modes of variability with conflicting periods (Weatherly 1993;Fu et al 2001;Hughes et al 2007).…”
Section: Introductionmentioning
confidence: 84%
“…In the first part of this study (Weijer et al 2007, hereinafter Part I), statistical analyses of altimeter data suggested that more than one mode of variability may be present in the Argentine Basin. This conclusion may reconcile several studies reporting on modes of variability with conflicting periods (Weatherly 1993;Fu et al 2001;Hughes et al 2007).…”
Section: Introductionmentioning
confidence: 84%
“…Possible regions of interest where these results may apply, are semi-enclosed basins and marginal seas, where variability in the form of high-frequency barotropic oscillations suggestive of Rossby basin modes has been observed (Warren et al, 2002;Weijer et al, 2007a;Fu et al, 2001;Stanev and Rachev, 1999).…”
Section: Introductionmentioning
confidence: 83%
“…For a basin the size of the Atlantic or the Pacific Ocean however the periods of the barotropic Rossby basin modes are too short (O(15days) or less) to be resolved by the altimetry data -the Topex/Poseidon has a 20-day Nyquist period, (Le Traon and Morrow, 2000). However, barotropic oscillations consistent with Rossby basin modes have been observed in basins semi-enclosed by bathymetry (Warren et al, 2002;Fu et al, 2001;Weijer et al, 2007a) and marginal seas (Stanev and Rachev, 1999).…”
Section: Temporal Variability Dominated By Barotropic Basin Modesmentioning
confidence: 90%
See 2 more Smart Citations